Lucille Cairns. Francophone Jewish Writers: Imagining Israel. Liverpool: Liverpool UP, 2015. - Alessandra Benedicty-Kokken (Studies in 20th & 21st Century Literature, 2018)
Review of Lucille Cairns. Francophone Jewish Writers: Imagining Israel. Liverpool: Liverpool UP, 2015. x + 310 pp.
Keywords: Jewish; Israel; Palestine; Mizrahi; Ashkenazi; Sephardi; French; literature; France; affect